Central Giant Cell Granuloma - Vikash Ranjan; M K Sunil; Sophia Kurien; Raghav Kumar; Ganapathi Moger (Wolters Kluwer Medknow Publications, 2010)
Central giant cell granuloma is an uncommon, benign, and proliferative lesion whose etiology is not defined. It is considered widely to be a non-neoplastic lesion Although formerly designated as giant cell reparative granuloma these lesions were found to be destructive rather than reparative, the word "reparative" was omitted from the ten and the terminology is central giant cell granuloma Presenting a case report of a female patient of aged 40 years having chief complaint of swelling since t year and pain since 4 to 5 months present at the lower right back region of the jaw. Correlating all clinical features and all investigation we finally diagnosed this case as central giant cell granuloma.